Penerapan Metode Laplacian Of Gaussian Dalam Mendeteksi Tepi Citra Pada Penyakit Meningitis - Rocky Haryono (STMIK Budi Darma, 2020)
Meningitis is an infectious disease of the meninges (protective membranes) that envelops the brain and spinal cord. When inflamed, the meninges swell because of an infection that occurs. The nervous system and brain can be damaged in some cases. Three symptoms of meningitis that need to be watched out for are fever, headache, and neck that feels stiff. Detection of the image edge of meningitis is an early form of treatment for the disease. Meningitis edge detection is done to identify the geometric area of ??meningitis. One of the edge detection methods that can be used is the Laplacian of Gaussian (LoG) method. In the LoG edge detection method there are several steps that need to be carried out, namely changing the original image (RGB) to gray (grayscale) then changing the gray image into a binary image and then performing the convolution operation of the binary image intensity matrix with the LoG filter. The results of this study indicate the detection of the edge of meningitis in the image using the Laplacian of Gaussian method produces sharp and thick edges. The meningitis edge is shown in the output image through white dots connected together to form a line